2023
DOI: 10.3390/w15061172
|View full text |Cite
|
Sign up to set email alerts
|

Decolourisation of Real Industrial and Synthetic Textile Dye Wastewater Using Activated Dolomite

Abstract: Textile effluent accounts for 22% of the total industrial wastewater produced in Malaysia. Due to their ubiquitous use in organic dyes, inefficiently treated textile wastewaters pose environmental and health hazards. Colour, chemical oxygen demand, biochemical oxygen demand, toxic metals and microbes are the commonly targeted water quality parameters in untreated textile fluids. Furthermore, their non-biodegradability and high colour intensity may reduce aquatic diversity by blocking the sunlight. Recently, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition to clay minerals, carbonate minerals such as calcite (Cal) and dolomite (Dol) were also studied for the removal of color dyes before and after heat treatment. Previous results showed that Dol will decompose into Cal, magnesium oxide, and carbon dioxide at temperatures of 700 • C [10,11], 800 • C [12,13], or 900 • C [14]. Dol heated at 800 • C for 4 h was evaluated for the removal of dyes basic violet 16 ) from initial concentrations of 10 to 50 mg/L (constant mass volume ratio of 1.5 g/0.5 L of solution) [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to clay minerals, carbonate minerals such as calcite (Cal) and dolomite (Dol) were also studied for the removal of color dyes before and after heat treatment. Previous results showed that Dol will decompose into Cal, magnesium oxide, and carbon dioxide at temperatures of 700 • C [10,11], 800 • C [12,13], or 900 • C [14]. Dol heated at 800 • C for 4 h was evaluated for the removal of dyes basic violet 16 ) from initial concentrations of 10 to 50 mg/L (constant mass volume ratio of 1.5 g/0.5 L of solution) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Dol heated at 800 • C for 4 h was evaluated for the removal of dyes basic violet 16 ) from initial concentrations of 10 to 50 mg/L (constant mass volume ratio of 1.5 g/0.5 L of solution) [15]. Also, Dol heated for 5 h at 300, 700, and 900 • C was evaluated for the removal of methyl orange (MO), C.I.13025, (C 14 H 14 N 3 NaO 3 S) [14]. In a binary solution made of reactive black 5 (RB5) and Congo red (CR), Dol treated at 900 • C showed preferential adsorption of CR over RB5 and was attributed to inner-sphere complexation with amine groups since CR and RB5 contain two vs. one amine functional groups [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previously mentioned minerals, carbonated minerals such as calcite (Cal) and dolomite (Dol) were also evaluated for their removal of color dyes before and after heat treatment. For example, Dol heated to 800 • C was tested for the removal of single and binary dyes [28], and Dol heated to 300, 700, and 900 • C was tested for the removal of an anionic dye, methyl orange (MO) [29]. Because of the strong affinity of ARS for calcium and phosphorus, CaCO 3 and H 3 PO 5 were utilized to synthesize calcium phosphate hydroxyapatite (Ca-Hap), which was tested for its removal of ARS under different physical and chemical conditions [30].…”
Section: Introductionmentioning
confidence: 99%